Anti-sulfurization LED packaging process and anti-sulfurization LED lamp bead

By applying anti-sulfurization liquid on the silver-plated layer of the LED bracket and baking it to form a anti-sulfurization layer, the problem that existing LED packaging glue cannot effectively prevent sulfur gas erosion is solved, effectively protecting the LED lamp beads and extending its service life.

CN118841492BActive Publication Date: 2025-04-25SHENZHEN ZDM OPTO-ELECTRONICS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410830360.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-04-25
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The existing LED packaging glue has poor gas barrier properties and cannot effectively prevent sulfur from eroding the silver substrate, resulting in the formation of silver sulfide and affecting the life of LED lamp beads.

Method used

The anti-sulfurization liquid is dotted with an automatic dispenser to the silver-plated layer inside the LED bracket, and bake it in the oven to form a anti-sulfurization layer, with the thickness controlled between 10-50nm.

Benefits of technology

While keeping the LED luminous flux and color temperature unchanged, the sulfur resistance of the silver substrate is significantly improved, and the erosion of sulfur gas on LED lamp beads is delayed, thereby improving the service life of LED lamp beads.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118841492B_ABST
    Figure CN118841492B_ABST
Patent Text Reader

Abstract

The present application belongs to the field of LED packaging technology, and the present application discloses an anti-sulfurization LED packaging process and an anti-sulfurization LED lamp bead. The anti-sulfurization LED packaging process in the present application includes the following steps: solid crystal, wire welding, spot coating of anti-sulfurization liquid, glue dispensing and baking, wherein the spot coating of anti-sulfurization liquid includes the following steps: adding anti-sulfurization liquid to the container, adjusting the glue dispensing machine to control the amount of spot coating, glue supply pressure and number of spot coatings, and baking. The present application accurately uses a spot coating anti-sulfurization process when coating the silver-plated surface of the LED bracket with anti-sulfurization liquid, and covers the silver-plated surface of the LED bracket with an anti-sulfurization layer, which can obviously delay the attenuation of the LED lamp bead, so that the LED lamp bead can maintain stable performance even in harsh environments.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of LED packaging technology, and in particular to an anti-sulfurization LED packaging process and an anti-sulfurization LED lamp bead. Background Art

[0002] LED has the advantages of long working life, low power consumption and fast response time, so it is widely used in the field of automotive lighting equipment. The LED lighting devices used in automotive lighting are usually high-power LED lighting devices, and usually use silicone encapsulant with better aging resistance and temperature resistance. However, silicone encapsulant has poor gas barrier performance and has disadvantages such as moisture permeability, oxygen permeability, sulfur permeability and bromine permeability. It cannot prevent the gas from corroding the underlying silver substrate, especially the corrosion of sulfur gas. Silver reacts with sulfur gas to form silver sulfide, which causes the silver layer to turn black and rapidly increases the light decay, directly affecting the life of LED components.

[0003] In order to ensure that LED lamp beads can maintain stable performance in harsh environments, anti-sulfurization treatment is required. The existing technology usually coats a curable glue composition, such as a silicone rubber composition, a metal-containing silicone composition, etc., on the wafer of the LED lamp bead to achieve the desired protective effect. However, after the coating is cured, the coating often reaches several microns or hundreds of microns. A thicker coating will seriously affect the light transmittance. Therefore, it is necessary to develop an anti-sulfurization LED packaging process with high coating liquid precision, good product reliability, and good anti-sulfur effect, to delay the erosion of sulfur gas on the LED lamp beads, thereby greatly increasing the service life of the LED lamp beads. Summary of the invention

[0004] In order to solve the above technical problems, an anti-sulfurization LED packaging process is developed to greatly improve the anti-sulfur performance of the silver substrate inside the LED bracket while keeping the optical properties such as LED luminous flux and color temperature unaffected. The present application provides an anti-sulfurization LED packaging process and anti-sulfurization LED lamp beads.

[0005] In a first aspect, the present application provides an anti-sulfurization LED packaging process, comprising the following steps:

[0006] S1. Use solid crystal glue to fix the LED chip inside the LED bracket;

[0007] S2, use a wire bonding machine to electrically connect the LED chip and the LED bracket;

[0008] S3, use an automatic dispensing machine to apply the anti-sulfurization liquid to the silver-plated layer inside the LED bracket, and bake it in an oven to form an anti-sulfurization layer;

[0009] S4, pouring encapsulation glue into the interior of the LED bracket, so that the encapsulation glue covers the surface of the LED chip and the anti-sulfurization layer to form an encapsulation glue layer; S5, putting the LED bracket after the glue filling in step S4 into an oven for secondary baking to form an LED semi-finished product, and cutting the LED semi-finished product into single pieces to obtain anti-sulfurization LED lamp beads.

[0010] Furthermore, the step S3 specifically includes the following steps:

[0011] S310, adding the anti-sulfurization liquid into the container of the automatic dispensing machine, the added amount being 30-60% of the volume of the container;

[0012] S320, adjust the atomizing valve body of the automatic dispensing machine to control the dispensing amount, and adjust the pressure point injection valve to control the glue supply pressure;

[0013] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2 and controlling the number of times of application for each LED bracket;

[0014] S340, putting the LED bracket coated with the anti-sulfurization liquid into the oven, controlling the temperature to 140-180°C, the time to 25-50 minutes, and baking to form an anti-sulfurization layer.

[0015] Furthermore, the anti-sulfurization layer has a thickness of 10-50 nm.

[0016] Furthermore, in step S310, the container is a plastic syringe, and the volume of the plastic syringe is 70-100 ml.

[0017] Furthermore, after the anti-sulfurization liquid is added to the plastic syringe, the usage time of the anti-sulfurization liquid in the plastic syringe is ≤40 minutes, and the usage time of each plastic syringe is ≤4 hours.

[0018] Furthermore, in step S320, the atomizing valve of the automatic dispensing machine is adjusted to control the dispensing amount of the nozzle to be 2.0×10 -6 -3.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 30-80MPa.

[0019] Preferably, in step S320, the atomizing valve body of the automatic dispensing machine is adjusted to control the dispensing amount of the nozzle to be 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 40MPa.

[0020] The glue supply air pressure is the internal air pressure of the plastic syringe after the anti-sulfurization liquid is added.

[0021] Anti-sulfur liquid is a highly fluid liquid. Improper setting of the glue supply pressure of the pressure-point injection valve will cause the anti-sulfur liquid to splash and cause machine pollution. Therefore, it is necessary to control the glue supply pressure of the pressure-point injection valve. More importantly, the inventors have found through experiments that improper setting of the glue supply pressure will cause the working voltage of the anti-sulfur LED lamp beads to be abnormal. The difference in the defective rate of products made with appropriate glue supply pressure and inappropriate glue supply pressure due to voltage abnormality can reach 20%.

[0022] As a result, the yield rate of the anti-sulfurization LED lamp beads is greatly reduced.

[0023] Furthermore, in step S330, the number of times of coating each LED bracket is controlled to be 3-5 times.

[0024] Preferably, in step S330, the number of times of coating each LED bracket is controlled to be 4 times.

[0025] By adopting the above technical solution, the amount of anti-sulfurization liquid applied is controlled by controlling the number of application times. In the present application, the number of application times of each LED bracket is controlled at 4 times, which is the conventional number of application times and the most mature number of application times. The inventor improves and adjusts the supporting process parameters. When the number of application times of each LED bracket is controlled at 3 or 5 times, the luminous flux of the anti-sulfurization LED lamp beads prepared does not change significantly. At the same time, the x and y offset values ​​of the CIE1931 color coordinates of each sample are small, and the target graph landing points of the CIE1931 color coordinates corresponding to the three different numbers of application times are similar. Therefore, when other conditions remain unchanged and only the number of application times of each LED bracket is controlled at 3 or 5 times, the optical performance of the anti-sulfurization LED lamp beads prepared will not be significantly affected.

[0026] Furthermore, the time interval between step S330 and step S340 is ≤30 minutes.

[0027] Furthermore, the anti-sulfurization liquid is selected from the S-BARRIER series anti-sulfurization material of Shin-Etsu Chemical Industry Co., Ltd.

[0028] In a second aspect, the present application provides anti-sulfurization LED lamp beads prepared by the above-mentioned anti-sulfurization LED packaging process.

[0029] In summary, the present invention includes at least one of the following beneficial technical effects:

[0030] 1. This application precisely adjusts the step of spot coating of anti-sulfurization liquid in the anti-sulfurization LED packaging process, thereby covering a layer of anti-sulfurization layer on the silver-plated surface of the LED bracket, which can significantly delay the attenuation of the LED lamp beads and enable the LED lamp beads to maintain stable performance even in harsh environments.

[0031] 2. This application uses a precise spot coating anti-sulfurization process when coating the silver-plated surface of the LED bracket with anti-sulfurization liquid. Compared with the traditional spray-coating anti-sulfurization process, on the one hand, the thickness of the anti-sulfurization layer after drying is thinner, which will not affect the adhesion performance of the packaging glue. On the other hand, the anti-sulfurization layer obtained by the spot coating anti-sulfurization process is more uniform, and the overall airtightness of the LED lamp beads is better after dispensing, thereby improving the product reliability. In addition, the spot coating anti-sulfurization process consumes less anti-sulfurization liquid, which is conducive to cost savings. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 From left to right in the figure are CIE1931 color coordinate measurement diagrams of 20 samples of Example 1, Example 2 and Example 3;

[0033] Figure 2 From left to right in the figure are CIE1931 color coordinate measurement diagrams of 1200 samples of Example 1, Example 2 and Example 3. DETAILED DESCRIPTION

[0034] The present application is further described in detail below with reference to the accompanying drawings and embodiments.

[0035] This application designs an anti-sulfurization LED packaging process, including the following steps:

[0036] S1. Use solid crystal glue to fix the LED chip inside the LED bracket;

[0037] S2, use a wire bonding machine to electrically connect the LED chip and the LED bracket;

[0038] S3, use an automatic dispensing machine to apply the anti-sulfurization liquid to the silver-plated layer inside the LED bracket, and bake it in an oven to form an anti-sulfurization layer;

[0039] S4, pouring encapsulation glue into the interior of the LED bracket, so that the encapsulation glue covers the surface of the LED chip and the anti-sulfurization layer to form an encapsulation glue layer; S5, putting the LED bracket after the glue filling in step S4 into an oven for secondary baking to form an LED semi-finished product, and cutting the LED semi-finished product into single pieces to obtain anti-sulfurization LED lamp beads.

[0040] The present application also designs an anti-sulfurization LED lamp bead produced by the above-mentioned anti-sulfurization LED packaging process.

[0041] Example 1

[0042] The anti-sulfurization LED packaging process in Example 1 includes the following steps:

[0043] S1. Use solid crystal glue to fix the LED chip inside the LED bracket;

[0044] S2, use a wire bonding machine to electrically connect the LED chip and the LED bracket;

[0045] S3, use an automatic dispensing machine to apply the anti-sulfurization liquid to the silver-plated layer inside the LED bracket, and bake it in an oven to form an anti-sulfurization layer;

[0046] S4, pouring encapsulation glue into the interior of the LED bracket, so that the encapsulation glue covers the surface of the LED chip and the anti-sulfurization layer to form an encapsulation glue layer; S5, putting the LED bracket after the glue filling in step S4 into an oven for secondary baking to form an LED semi-finished product, and cutting the LED semi-finished product into single pieces to obtain anti-sulfurization LED lamp beads.

[0047] Wherein, step S3 specifically includes the following steps:

[0048] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0049] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 40MPa;

[0050] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2, and controlling the number of times of application for each LED bracket to be 4 times;

[0051] S340. After the anti-sulfurization liquid is applied, the LED bracket must be placed in the oven for baking within 30 minutes. The LED bracket after the anti-sulfurization liquid is applied is placed in the oven, the temperature is controlled at 150°C, the time is 30 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 40nm.

[0052] In Example 1, the die-bonding adhesive in step S1 is Shin-Etsu KER-3200-T7, and the LED bracket is Derun 4014PCT (24*28), wherein the thickness of the silver-plated layer on the LED bracket is 60um, the wire used in the wire bonding machine is 0.9mil gold wire, and the LED chip is Jucan F2639A chip; the anti-sulfurization liquid in step S3 is Shin-Etsu S-BARRIER-01 anti-sulfurization material; the packaging adhesive in step S4 is Shin-Etsu LPS-5555A.

[0053] Example 2

[0054] Embodiment 2 is based on Embodiment 1, except that step S3 of Embodiment 2 is changed to:

[0055] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0056] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 40MPa;

[0057] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2, and controlling the number of times of application for each LED bracket to be 3 times;

[0058] S340. After the anti-sulfurization liquid is applied, the LED bracket must be placed in the oven for baking within 30 minutes. The LED bracket after the anti-sulfurization liquid is applied is placed in the oven, the temperature is controlled at 150°C, the time is 30 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 10nm.

[0059] Example 3

[0060] Embodiment 3 is based on Embodiment 1, except that step S3 of Embodiment 3 is changed to:

[0061] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0062] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 40MPa;

[0063] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2, and controlling the number of times of application for each LED bracket to be 5 times;

[0064] S340. After the anti-sulfurization liquid is applied, the LED bracket must be placed in the oven for baking within 30 minutes. The LED bracket after the anti-sulfurization liquid is applied is placed in the oven, the temperature is controlled at 150°C, the time is 30 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 80nm.

[0065] Example 4

[0066] Embodiment 4 is based on Embodiment 1, except that step S3 of Embodiment 4 is changed to:

[0067] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0068] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 40MPa;

[0069] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2, and controlling the number of times of application for each LED bracket to be 4 times;

[0070] S340. After the anti-sulfurization liquid is applied, the LED bracket must be placed in the oven for baking within 30 minutes. The LED bracket after the anti-sulfurization liquid is applied is placed in the oven, the temperature is controlled at 140°C, the time is 50 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 40nm.

[0071] Example 5

[0072] Embodiment 5 is based on Embodiment 1, except that step S3 of Embodiment 5 is changed to:

[0073] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0074] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 40MPa;

[0075] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2, and controlling the number of times of application for each LED bracket to be 4 times;

[0076] S340. After the anti-sulfurization liquid is applied, the LED bracket must be placed in the oven for baking within 30 minutes. The LED bracket after the anti-sulfurization liquid is applied is placed in the oven, the temperature is controlled at 180°C, the time is 25 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 40nm.

[0077] Example 6

[0078] Embodiment 6 is based on Embodiment 1, except that step S3 of Embodiment 6 is changed to:

[0079] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0080] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6mL / time, adjust the pressure point injection valve to control the glue supply pressure to 30MPa;

[0081] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2, and controlling the number of times of application for each LED bracket to be 4 times;

[0082] S340. After the anti-sulfurization liquid is applied, the LED bracket must be placed in the oven for baking within 30 minutes. The LED bracket after the anti-sulfurization liquid is applied is placed in the oven, the temperature is controlled at 150°C, the time is 30 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 40nm.

[0083] Example 7

[0084] Embodiment 7 is based on Embodiment 1, except that step S3 of Embodiment 7 is changed to:

[0085] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0086] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 75MPa;

[0087] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2, and controlling the number of times of application for each LED bracket to be 5 times;

[0088] S340. After the anti-sulfurization liquid is applied, the LED bracket must be placed in the oven for baking within 30 minutes. The LED bracket after the anti-sulfurization liquid is applied is placed in the oven, the temperature is controlled at 150°C, the time is 30 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 80nm.

[0089] Example 8

[0090] Embodiment 8 is based on Embodiment 1, except that step S3 of Embodiment 8 is changed to:

[0091] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0092] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 80MPa;

[0093] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2, and controlling the number of times of application for each LED bracket to be 3 times;

[0094] S340. After the anti-sulfurization liquid is applied, the LED bracket must be placed in the oven for baking within 30 minutes. The LED bracket after the anti-sulfurization liquid is applied is placed in the oven, the temperature is controlled at 150°C, the time is 30 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 10nm.

[0095] Comparative Example 1

[0096] Comparative Example 1 is based on Example 1, except that the LED lamp beads in Comparative Example 1 are not subjected to anti-sulfurization treatment, that is, the preparation process of the LED lamp beads in Comparative Example 1 includes the following steps:

[0097] S1. Use solid crystal glue to fix the LED chip inside the LED bracket;

[0098] S2, use a wire bonding machine to electrically connect the LED chip and the LED bracket;

[0099] S3, pouring the encapsulation glue into the interior of the LED bracket, so that the encapsulation glue covers the surface of the LED chip and the silver-plated layer to form an encapsulation glue layer;

[0100] S4, putting the LED bracket after glue filling in step S3 into an oven for baking to form an LED semi-finished product, and cutting the LED semi-finished product into single pieces to obtain anti-sulfurization LED lamp beads.

[0101] Comparative Example 2

[0102] Comparative Example 2 is based on Example 1, except that step S3 in Comparative Example 2 is changed to:

[0103] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0104] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 95MPa;

[0105] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2, and controlling the number of times of application for each LED bracket to be 3 times;

[0106] S340. After the anti-sulfurization liquid is applied, the LED bracket must be placed in the oven for baking within 30 minutes. The LED bracket after the anti-sulfurization liquid is applied is placed in the oven, the temperature is controlled at 150°C, the time is 30 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 10nm.

[0107] Comparative Example 3

[0108] Comparative Example 3 is based on Example 1, except that step S3 in Comparative Example 3 is changed to:

[0109] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0110] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 40MPa;

[0111] S330, using an automatic dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the treatment in step S2, and controlling the number of times of application for each LED bracket to be 6 times;

[0112] S340. After the anti-sulfurization liquid is applied, the LED bracket must be placed in the oven for baking within 30 minutes. The LED bracket after the anti-sulfurization liquid is applied is placed in the oven, the temperature is controlled at 150°C, the time is 30 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 130nm.

[0113] Comparative Example 4

[0114] Comparative Example 4 is based on Example 1, except that step S3 in Comparative Example 4 is changed to:

[0115] S310, adding the anti-sulfurization liquid into the plastic syringe of the automatic dispensing machine, the added amount is 60% of the volume of the plastic syringe, and the volume of the plastic syringe is 80 ml;

[0116] S320, adjust the atomizing valve of the automatic dispensing machine to control the dispensing amount to 2.5×10 -6 mL / time, adjust the pressure point injection valve to control the glue supply pressure to 40MPa;

[0117] S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2, and controlling the number of times of application for each LED bracket to be 4 times;

[0118] S340, after the LED bracket with anti-sulfurization liquid is applied, it is placed in an oven for baking after being allowed to stand for 60 minutes. The LED bracket with anti-sulfurization liquid applied is placed in an oven, the temperature is controlled at 150°C, the time is 30 minutes, and baking is performed to form an anti-sulfurization layer. The thickness of the anti-sulfurization layer is about 40nm.

[0119] Performance Testing

[0120] 1. The luminous flux of the LED lamp beads prepared in Examples 1-8 and Comparative Examples 1-4 was measured with reference to the standard GB / T26178-2010 "Method for measuring luminous flux". The measurement results are shown in Table 1.

[0121] 2. The LED lamp beads prepared in Examples 1-8 and Comparative Examples 1-4 were subjected to a sulfurization experiment. The sulfurization experiment conditions were as follows: the dosage of potassium sulfide pentahydrate was 2.5 g / L, the sulfurization temperature was 105°C, and the sulfurization time was 2 h. The luminous flux of the LED lamp beads prepared in Examples 1-8 and Comparative Examples 1-4 after sulfurization was tested. The measurement results are shown in Table 1.

[0122] 3. The LED lamp beads prepared in Examples 1-8 and Comparative Examples 1-4 were subjected to a current-voltage stability test. The test method was as follows: the voltage across the LED lamp beads was tested at a rated current. In the present application, the rated current was set to 120 mA. When the average voltage measurement value of the LED lamp beads was higher than 3.1 V, the voltage was abnormal and the LED lamp beads were defective and scrapped. 1,200 samples were measured for each example or comparative example, and the voltage defect rate was statistically analyzed. The measurement results are shown in Table 1.

[0123] 3. The x and y offsets of the color coordinates of the LED lamp beads prepared in Examples 1-8 and Comparative Examples 1-4 after vulcanization were measured. The measurement results are shown in Table 1.

[0124] 4. The LED lamp beads prepared in Examples 1-3 were analyzed by CIE chromaticity space. Several samples were taken from each example to measure CIE1931 color coordinates. The measurement results are shown in Figure 1 and Figure 2 ; Figure 1 The number of test samples for each embodiment is 20. Figure 2 The number of test samples for each embodiment is 1200.

[0125] Table 1

[0126]

[0127] Through Figure 1 and Figure 2 After analysis, there is no significant difference in the target landing points of Examples 1, 2, and 3, that is, the x and y offsets are similar. While keeping the dot coating constant, reducing or increasing the dot coating times by 1 has no significant effect on the color coordinates of the obtained LED lamp beads.

[0128] By analyzing Table 1, the anti-sulfurization liquid spot coating process of the present application has no obvious effect on the brightness and color coordinates of the LED lamp beads; when the glue supply pressure is too high or there are problems in other processes, the number of samples with abnormal voltage of the prepared LED lamp beads will increase dramatically. The voltage of the LED lamp is too high under rated current, which can easily cause damage to the LED lamp beads. Therefore, the anti-sulfurization liquid should be spot coated on the LED bracket in strict accordance with the corresponding parameters.

[0129] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A sulfur-resistant LED packaging process, characterized in that: The following steps are involved: S1. Use solid crystal glue to fix the LED chip inside the LED bracket; S2, use a wire bonding machine to electrically connect the LED chip and the LED bracket; S3, use an automatic dispensing machine to apply the anti-sulfurization liquid to the silver-plated layer inside the LED bracket, and bake it in an oven to form an anti-sulfurization layer; S4, pouring the encapsulation glue into the interior of the LED bracket, so that the encapsulation glue covers the surface of the LED chip and the anti-sulfurization layer to form an encapsulation glue layer; S5, putting the LED bracket after the glue filling in step S4 into an oven for secondary baking to form an LED semi-finished product, and cutting the LED semi-finished product into single pieces to obtain anti-sulfurization LED lamp beads; The step S3 specifically comprises the following steps: S310, adding anti-sulfurization liquid into the container of the automatic dispensing machine, the added amount being 30-60% of the container volume; S320, adjust the atomizing valve body of the automatic dispensing machine to control the dispensing amount, and adjust the pressure point injection valve to control the glue supply pressure; S330, using an automatic glue dispensing machine to apply anti-sulfurization liquid to the silver-plated layer inside the LED bracket after the processing in step S2 and controlling the number of times of application for each LED bracket; S340, putting the LED bracket coated with the anti-sulfurization liquid into an oven, controlling the temperature to 140-180° C. for 25-50 minutes, and baking to form an anti-sulfurization layer; In the step S320, the pressure point injection valve is adjusted to control the glue supply pressure to 30-80 MPa; In the step S330, the number of times of coating each LED bracket is controlled to be 3-5 times; The time interval between step S330 and step S340 is ≤30 minutes.

2. The anti-sulfurization LED packaging process according to claim 1, characterized in that: In step S310, the container is a plastic syringe, and the volume of the plastic syringe is 70-100 ml.

3. The anti-sulfurization LED packaging process according to claim 2, characterized in that: After the anti-sulfurization liquid is added to the plastic syringe, the usage time of the anti-sulfurization liquid in the plastic syringe is ≤40min, and the usage time of each plastic syringe is ≤4h.

4. The anti-sulfurization LED packaging process according to claim 2, characterized in that: In step S320, the atomizing valve of the automatic dispensing machine is adjusted to control the dispensing amount of the nozzle to 2.0×10 -6 -3.5×10 -6 mL / time.

5. The anti-sulfurization LED packaging process according to claim 1, characterized in that: The anti-sulfurization liquid is selected from the S-BARRIER series anti-sulfurization material of Shinetsu Chemical Industry Co., Ltd.

6. An anti-sulfurization LED lamp bead made by the anti-sulfurization LED packaging process described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Dispensing process

    CN103331248A

  • Full-spectrum LED for field of display backlight

    CN112216779A

  • Protection type LED packaging method and protection type LED lamp bead

    CN115706194A